Pre-emptive analgesia with diclofenac in combination with ketamine in patients undergoing laparoscopic cholecystectomy - Soni, Vikas; Gupta , Suman; Deepak Singh Gurjar,; Nancy Ekka,; Verma , Gargi (Asian Journal of Medical Sciences, 2025)
Background: Laparoscopic cholecystectomy is a minimally invasive surgery which most often is associated with post-operative pain. Pre-emptive administration of ketamine and diclofenac in combination reduces post-operative pain.Aims and Objectives: In patients undergoing laparoscopic cholecystectomy, the aim of this study was to evaluate the efficacy of preemptively administered ketamine and diclofenac and their combination on post-operative pain.Materials and Methods: A total of 90 patients, with American Society of Anesthesiologists physical grading I and II, were recruited for the study. Patients were allocated randomly into the following groups: Group I was administered 100 mL isotonic saline intravenous (IV) 20 min before the induction of anesthesia and 0.15 mg/kg ketamine IV diluted in 5-mL isotonic saline before skin incision; Group II received diclofenac in the dose of 1 mg/kg diluted in 100-mL isotonic saline IV 20 min before the induction of anesthesia and 5-mL isotonic saline IV before skin incision; Group III was administered a combination of diclofenac 1 mg/kg diluted in 100-mL isotonic saline IV 20 min before the induction of anesthesia and 0.15 mg/kg ketamine diluted in 5-mL isotonic saline IV before skin incision. Time for rescue analgesia, post-operative Visual Analog Scale score, hemodynamic changes, and adverse effects were evaluated.Results: Post-operative analgesia was longer in Group III as compared to Group II and Group I at 2, 4, and 6 h (P